Mechanism Analysis and Optimal Design of Return Impact of a Certain Aircraft Canopy Actuator - Jing Gao; Lingxiao Quan; Linshan Han; Chen Fu; Changhong Guo (Actuators)
During the closure of a specific aircraft canopy, oil leakage occurs from the pressure tank’s overflow port in the gas–liquid control system. This issue often occurs during closure, potentially leading to reduced system oil and impacting the normal operation of the canopy. Firstly, we analyzed canopy actuation principles to identify the return stroke pressure impact transmission path and derive its mathematical model. Secondly, the gas–liquid control system simulation model was constructed to replicate the oil overflow fault in the pressure tank digitally. Finally, specific improvement measures were developed based on fault mechanism analysis and simulation results to optimize the system’s design. After optimization, the peak pressure in the pressure tank’s oil chamber was reduced by 91.58%, eliminating overflow. This solution was validated by the manufacturer and implemented in production.